Peran Komite Sekolah dalam Meningkatkan Mutu Pendidikan - Asparingga, Ririn (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to analyze the role of the school committee in improving the quality of education at SDN 27 Palembang. The school committee has an important role as a strategic partner in developing the quality of education through support in aspects of policy, budget, and quality improvement programs. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study indicate that the school committee plays an active role in helping to provide facilities and infrastructure, supporting curriculum development activities, and contributing to training for teachers and staff. In addition, collaboration between the school committee, teachers, and parents helps strengthen an inclusive and effective education system, creating a conducive, adaptive, and student-oriented learning environment. Efforts to improve quality through the participation of this committee have been shown to increase student learning motivation and parent satisfaction with the school. With the increasingly strategic role of the committee, efforts to improve quality can be structured, systematic, and sustainable so as to produce long-term positive impacts on student development. The optimal role of the school committee is expected to continue to be improved through innovation, collaboration, and ongoing supervision, in order to encourage the achievement of quality education at SDN 27 Palembang.